Accurate and sensitive determination of harmful aromatic amine products of azo dyes in wastewater and textile samples by GC-MS after multivariate optimization of binary solvent dispersive liquid-liquid microextraction - Ozkan, Betul Cicek; Firat, Merve; Chormey, Dotse Selali; Bakirdere, Sezgin (ELSEVIER, 2019)
In this study, eight hazardous aromatic amine products of azo dyes were simultaneously determined by GC-MS in wastewater and textile samples after preconcentration with an accurate and sensitive binary solvent dispersive liquid-liquid microextraction method. A univariate optimization procedure was used to determine the most influential experimental parameters and a multivariate optimization was used to determine optimum amounts of each parameter. A model developed from experimented results was used to ascertain the effects of main parameters and their interaction effects with each other. The optimum parameters obtained from the model were chloroform (100 mu L), 1,2-dichloroethane (100 mu L), ethanol (2.0 mL) and vortex (15 s). The limits of detection (LOD) and quantification (LOQ) of the analytes determined under optimum conditions ranged between 0.16-1.4 mu g/L and 0.53-4.6 mu g/L, respectively. The calibration plots of the analytes were linear (R-2 > 0.9991) over a broad range and the %RSDs were below 10%. The method was applied to wastewater and textile samples as a test of the method's applicability and accuracy. The percent recovery obtained for wastewater by the standard calibration method was appreciable (85-109%), but procedural matrix matching was used to improve the percent recovery for the textile sample (85-103%).
Keywords: Azo dyes; Aromatic amines; GC-MS; DLLME; DIODE-ARRAY DETECTION; MASS-SPECTROMETRY; DEGRADATION; EXTRACTION; REDUCTION; SORBENT; Chemistry